Ensino de inglês para alunos surdos: materiais didáticos e estratégias de ensino. - Spasiani, Monique Vanzo (2018)
Despite the increasing recognition on the topics of diversity and on the issues of deafness, the teaching and learning of Foreign Language (FL) by deaf students in Brazil still present problems, especially regarding the absence of certified professionals to work with such audience, which makes it a process based on instructional material (IM) available to the teacher, such as the textbook (TB) - not yet specifically developed for the education of deaf people. Researches point to the importance of the IMs in teaching-learning of a FL and to the question that their choice/elaboration/adaptation should be conscious and coherent to the group of students they are destined for (TOMLINSON, 2001; ALMEIDA FILHO, 2013; etc.). From this perspective, in a qualitative-interpretative way and through a case study (YIN, 2005), we investigated, with this study, which characteristics aspects present in the IM and teaching strategies (TE) make them favorable to the learning of English language as FL by deaf students, considering the educational needs of such audience. Therefore, the English language (EL) classes of a mixed group (deaf and hearing students) of the 8th grade of an inclusive public school were observed and recorded in a research journal. In addition, with the aid of questionnaires combined with interviews with deaf students, Brazilian Sign Language educational interpreters and English teacher, we reflected about the types of IMs and TE that are pertinent to this context in order to support the teacher's work and to not leave her/him at the mercy of TB. Based on some authors such as Lacerda, Santos and Caetano (2014), Sousa (2008, 2015) and Almeida Filho (1993, 2013), the analysis of the data suggested that there are two important axes in which the IMs and TE must be based on to be potent in FL education for the deaf: visuality and the parallel between languages, always focusing on the target foreign-language and through a communicative perspective. In addition, resources such as images in their traditional meaning, videos and films, the use of the blackboard, tables, concept maps, illustrated dictionaries, mock-ups, slide shows, digital technologies and the writings in the notebook and in the TB, if supported by the axes described and directed to their target audience, can be very useful and positive to the process of teaching and learning English as FL by deaf students. Finally, the aim was to defend the teaching of EL as a mean of social inclusion, since only inserting deaf students into the school space of hearing ones or guaranteeing the presence of a Brazilian Sign Language interpreter in the classroom, but not allowing them access to methodological resources that could facilitate their learning, does not mean an appropriate inclusion (ROSA, 2006; LACERDA, 2006). It is understood that the results achieved here can greatly contribute to the pedagogical practices of professionals in the area of Special Education and FL teaching, as well as teachers and future teachers of deaf students, with the purpose of presenting them different ways of dealing with these students in the classroom and making them reflect on the importance and role of teaching materials and specific teaching strategies in that context.